Steric constraints as folding coadjuvant - Tarragó, M. E.P.; Rocha, Luiz F. O. [UNESP]; daSilva, R. A.; Caliri, A. (American Physical Society (APS), 2003)
Through the analyses of the Miyazawa-Jernigan matrix it has been shown that the hydrophobic effect generates the dominant driving force for protein folding. By using both lattice and off-lattice models, it is shown that hydrophobic-type potentials are indeed efficient in inducing the chain through nativelike configurations, but they fail to provide sufficient stability so as to keep the chain in the native state. However, through comparative Monte Carlo simulations, it is shown that hydrophobic potentials and steric constraints are two basic ingredients for the folding process. Specifically, it is shown that suitable pairwise steric constraints introduce strong changes on the configurational activity, whose main consequence is a huge increase in the overall stability condition of the native state; detailed analysis of the effects of steric constraints on the heat capacity and configurational activity are provided. The present results support the view that the folding problem of globular proteins can be approached as a process in which the mechanism to reach the native conformation and the requirements for the globule stability are uncoupled. © 2003 The American Physical Society.